WHISTLEBLOWING FOR VILLAGE MANAGEMENT OF VILLAGE FUNDS: DYNAMICS AND CHALLENGES - Utami, Intiyas (Faculty of Business, Widya Mandala Catholic University Surabaya, Indonesia, 2018)
This study aims to describe the dynamics of potential whistleblowers for fraud in village fund management. This research was conducted in all villages in the Kledung Subdistrict, Temanggung Regency as the largest tobacco producing area in Indonesia. The design of the study used descriptive qualitative with informants in the entire village of Kledung Subdistrict, Temanggung Regency, Central Java, Indonesia. The results of the study showed that in managing village funds, whistleblowers for fraudulent management of village funds could be carried out because of the courage of village fund managers. The challenges faced by whistleblowers are the need for mechanisms and safe reporting channels.